Use of a novel mobilizable vector to inactivate the scrA gene of Streptococcus sobrinus by allelic replacement. - Buckley, N D (1995)
The virulence factors of the cariogenic bacterium Streptococcus sobrinus have been difficult to assess because of a lack of tools for the genetic manipulation of this organism. The construction of an Escherichia coli-Streptococcus shuttle vector, pDL289, that can be mobilized into S. sobrinus by the conjugative plasmid pAM beta 1 was described in a previous report. The vector contains pVA380-1 for replication and mobilization in streptococci, the pSC101 replicon for maintenance in E. coli, a kanamycin resistance marker that functions in both hosts, and the multiple cloning site and lacZ from pGEM7Zf(-). pDL289 is stable with or without selection in several species of Streptococcus. In this study, a derivative with a deletion in the minus origin of the pVA380-1 component of pDL289 was constructed. This derivative, pDL289 delta 202, was less stable than pDL289 in Streptococcus gordonii Challis, Streptococcus mutans, and S. sobrinus. Both pDL289 and pDL289 delta 202 were mobilizable by pAM beta 1 into S. sobrinus, with frequencies of 3 x 10(-6) and 1 x 10(-7) transconjugants per recipient CFU, respectively. The cloned scrA gene of S. sobrinus 6715-10 coding for the EIISuc of the sucrose-specific phosphoenolpyruvate phosphotransferase system was interrupted by the insertion of a streptococcal spectinomycin resistance gene active in E. coli and streptococci. The interrupted scrA gene was subcloned into both pDL289 and pDL289 delta 202. Each recombinant plasmid was introduced into the DL1 strain of S. gordonii Challis, which was then used as a recipient for the conjugative transfer of pAM beta 1. The latter plasmid was used to mobilize each recombinant plasmid from S. gordonii Challis DL1 to S. sobrinus 6715-10RF. Subsequently, recombinants derived from a double-crossover event were isolated on the basis of resistance to spectinomycin and susceptibility to kanamycin. Recombinational events were confirmed by Southern hybridization, and the inactivation of the EII Suc in double crossovers was confirmed by phosphotransferase system assays. This is the first report of allelic replacement in S. sobrinus.